The complete chloroplast genome of Aconitum coreanum (H. Lév.) Rapaics (Ranunculaceae). Issue 2 (3rd July 2019) - Kim, Yongsung; Yi, Jae-Sun; Min, Juhyeon; Xi, Hong; Kim, Da Yeon; Son, Janghyuk; Park, Jongsun; Jeon, Jeong-Ill
Abstract: Aconitum coreanum (H. Lév.) Rapaics listed in the Korean Red List is a medicinal herb. We presented complete chloroplast genome, which is 157, 024 bp long and has four subregions: 87, 637 bp of large single-copy and 16, 901 bp of small single-copy regions, which are separated by two 26, 243 bp inverted repeat regions including 132 genes (86 protein-coding genes, 8 rRNAs, and 37 tRNAs). The overall GC content of the chloroplast is 38.0%. Phylogenetic trees show that A. coreanum occupied a basal position at subgenus Aconitum clade and two A. coreanum isolated from midwestern and eastern regions of Korea are clustered together.